The Detection of Cancer Epigenetic Traces in Cell-Free DNA - Koval, Anastasia P.; Blagodatskikh, Konstantin A.; Kushlinskii, Nikolay E.; Shcherbo, Dmitry S. (Frontiers in Oncology, 2021)
Nucleic acid fragments found in blood circulation originate mostly from dying cells and carry signs pointing to specific features of the parental cell types. Deciphering these clues may be transformative for numerous research and clinical applications but strongly depends on the development and implementation of robust analytical methods. Remarkable progress has been achieved in the reliable detection of sequence alterations in cell-free DNA, while decoding epigenetic information from methylation and fragmentation patterns requires more sophisticated approaches. This review discusses the currently available strategies for detecting and analyzing the epigenetic marks in the liquid biopsies.